An Upcycling Approach from Fruit Processing By-Products: Flour for Use in Food Products - Laís Benvenutti; Fernanda Moreira Moura; Gabriela Zanghelini; Cristina Barrera; Lucía Seguí; Acácio Antonio Ferreira Zielinski (Foods)
The growing global population has led to increased food consumption and a significant amount of food waste, including the non-consumed parts of fruits (e.g., stems, rinds, peels, seeds). Despite their nutrient richness, these by-products are often discarded. With the rising interest in nutrient-dense foods for health benefits, fruit by-products have potential as nutritious ingredients. Upcycling, which repurposes waste materials, is one solution. White flour, which is common in food products like bread and pasta, has good functional properties but poor nutritional value. This can be enhanced by blending white flour with fruit by-product flours, creating functional, nutrient-rich mixtures. This review explores using flours from common Brazilian fruit by-products (e.g., jaboticaba, avocado, guava, mango, banana, jackfruit, orange, pineapple, and passion fruit) and their nutritional, physical–chemical properties, quality and safety, and applications. Partially replacing wheat flour with fruit flour improves its nutritional value, increasing the amount of fiber, protein, and carbohydrates present in it. However, higher substitution levels can alter color and flavor, impacting the sensory appeal and acceptability. While studies showed the potential of fruit by-product flours in food formulation, there is limited research on their long-term health impacts.